Highway to economic growth? Competition in public works tenders in the Democratic Republic of Congo - Sergio Galletta; Mario Jametti; Agustin Redonda (Center for Economic Studies and ifo Institute (CESifo), 2012)
The Democratic Republic of Congo (DRC) is one of the poorest countries in the World. The construction sector will play an essential part to bring the country on the path of economic growth, and competition within the sector is crucial to achieve this goal. In this paper we analyze the effect of competition in public works tenders in the DRC. Using a unique and newly assembled database on tenders we find that the number of participating bidders and the observed spread of submitted bids both significantly reduce contract prices, confirming our prior that competitive pressure can enhance the overall performance of the sector.
Keywords: D44; L13; L74; 330; construction; competition; tenders; public works; Öffentlicher Bau; Ausschreibung; Wettbewerb; Bauwirtschaft; Wirtschaftliche Effizienz; Kongo (Demokratische Republik)